The IMPACT OF ENTREPRENEURIAL LEADERSHIP ON EMPLOYEE PERFORMANCE AT THE DEPARTMENT OF INDUSTRY AND TRADE OF JAMBI PROVINCE WITH INNOVATIVE WORK BEHAVIOR AS AN INTERVENING VARIABLE - Indriyani, Rima; Adriani, Zulfina; Khalik, Idham (Management Department, Faculty of Economics and Business, Universitas Jambi, 2024)
This study explores the impact of entrepreneurial leadership on innovative work behavior and employee performance within the public sector, focusing on the Jambi Province Industry and Trade Office—a critical entity in local economic development. Adopting a mixed-methods approach, the research involved a survey of 114 employees supplemented by qualitative observations, analyzed through Partial Least Squares Structural Equation Modeling (PLS-SEM). Findings indicate that entrepreneurial leadership significantly enhances innovative work behavior (Path coefficient = 0.63, p < 0.01), which in turn mediates the relationship between leadership and employee performance (Indirect effect = 0.27, p < 0.05). Additionally, the direct impact of entrepreneurial leadership on employee performance was also significant (Path coefficient = 0.36, p < 0.05), underscoring the dual pathways—direct and mediated—through which leadership styles conducive to innovation can improve organizational outcomes. These results underscore the transformative potential of entrepreneurial leadership in fostering innovation and enhancing performance within traditionally less dynamic public sector environments. The study contributes to the burgeoning literature on leadership in the public sector by demonstrating the pivotal role of leadership styles in enhancing innovation and operational efficiency.